The Impact of Virtual Reality (VR) on Improving Customer Experience: A Case Study of the Religious Tourism Sector (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This study aims to examine the impact of virtual reality (VR) technologies on enhancing customer experience in the religious tourism sector, though focusing on three main dimensions: the realism of the virtual environment, immersion in the virtual environment, and the sense of presence. The descriptive analytical approach was employed to collect and analyze data from a sample of 241 Generation Z individuals who are interested in religious tourism and have an experience using VR technologies. A questionnaire based on a five-point Likert scale was used to measure the influence of VR on customer experience. The results showed that the three dimensions significantly contribute to improving the customer experience. Realism had the greatest impact on increasing customer engagement with religious sites, while immersion enhanced the emotional depth of the experience. The sense of presence played a vital role in creating a realistic feeling of being at the actual location. Based on these findings, the study recommends promoting the use of VR technologies in religious tourism and investing in their development, as well as offering training programs for professionals to improve service quality and increase visitor satisfaction and loyalty
Keywords: Immersion in Virtual Environment; Feeling of Presence; Religious Tourism, Realism of Virtual Evironment; Virtual Reality Technologies.